Jawabanmu

2014-05-04T19:22:10+07:00
Lim    Sin2π(4x - 3)  =  lim    (8πx - 6π)
x ⇒+      x² + 3x            x⇒+   x(x + 3)
                               = lim    (Sin8πxCos6π - Cos8πxSin6π)
                                  x⇒+        x(x + 3)
                               = lim    Sin 8πx .
                                  x⇒+   x(x + 3) .8π
                               = lim       8π . Sin8πx
                                  x⇒+   (x+3)    8πx
                               = Lim    8π
                                  x⇒+  x + 3
                               = 
                                    +
                               = 0
keterangan untuk tanda + sebagai pengganti tak terdefinisi